High nitrogen use efficiency in wheat is explained by a longer fast-increase period and adequate pre-anthesis nitrogen accumulation - Yu, Minglong; Liu, Churong; Liu, Hongrun; Zhang, Yushi; Li, Zhaohu; Zhang, Mingcai (Frontiers in Plant Science, 2026)
IntroductionNitrogen (N)-efficient wheat cultivars achieve higher grain yields with equivalent N fertilizer inputs, and the grain filling character largely determines grain weight (GW) in cereal crops. However, the relationship of grain filling traits and N responsiveness (Nr) in wheat has not been fully evaluated.MethodsA two-year field experiment evaluated five wheat cultivars across varying N levels (0, 75, 150, and 225 kg N ha−1) to assess how grain filling traits and N-related characteristics influence Nr.ResultsThe results showed that N-responsiveness wheat cultivars exhibited higher grain yields and critical N supply, alongside lower chlorophyll degradation rates (CDR). The direct path coefficient of GW on yield was 0.478, which explained 85.2% of the yield variation and was negatively correlated with other yield components. Across the combinations of cultivar and N supply, the variation in GW was primarily driven by the duration of fast-increase period (Tfast), rather than by the duration of slow-increase period (Tslow) and slight-increase period (Tslight). Furthermore, the sensitivity of Tfast to N supply explained the Nr of grain yield in wheat. Structural equation modeling showed that adequate pre-anthesis N accumulation was the dominant factor driving the extension of Tfast in high N-responsiveness wheat cultivates, secondary to lower CDR, which ultimately resulted in the highest GW. In addition, prolonging Tfast induced enhanced post-anthesis N translocation in wheat, which contributed to higher N use efficiency (NUE).DiscussionProlonging the Tfast enhances N responsiveness in wheat grain yield, providing a novel framework for evaluating NUE. This finding also highlights the critical role of elevated N accumulation at anthesis under N fertilization.